Factors affecting degradation of barley straw in sacco and microbial activity in the rumen of cows fed fibre-rich diets. JI: The level of supplemental fishmeal (Semiárida, 2020)
A diet composed of 76.2% untreated barley straw + 23.8% rye grass hay was given to three nonlactating cows at 90% of ad libitum intake. The cows were supplemented via cannulae with three differents levels of fishmeal in arder to make the ration up to 8%, 10% and 14% crude protein on a dry-matter basis. Treatments were arranged in a Latin Square design. Nylon bags containing untreated barley straw were incubated in the rumen 01 the cows for up to 72 h. Degradability of dry matter, total organic matter and the individual components of the cell wall of barley straw were affected by the protein level of the dlel. The Inclusion of fishmeal to a Ievel of 14% dietary protein produced the highest degradability of all parameters measured. The protein level also affected ammonia and total VFA concentrations; both fermentation products were highest in the treatment with the high fishmeal level. Rumen pH and rumen outflow rate of Iiquid and particulate phases were not affected by protein level. The ATP concentration found in the solid residue, remaining after removal of the liquid phase from the rumen content, Increases with increasing fishmeal level., while ATP in the Iiquid phase remained unchanged. This indicates that, under the conditions of this study, fishmeal exerts its effects on the microbes intimately associated lo the fibre, and not upon the whole microbial population. The microbial DNA concentration of digesta nylon bags increased during the first 24 h of incubation and then decreased until the end of incubation, indicating a process of colonization and depletion of degradable substrates.Resúmenes de Trabajos presentados en otras publicaciones (por docentes de la UNLPam.), Publicado en Animal Feed Science Technology, 70: 11-22, 1998.
Keywords: protein level; straw degradation; rumen; cows